Morphological changes of the small intestine mucosa in HIV/mycobacterium tuberculosis coinfection - Todoriko, Liliia D.; Pidverbetska, Olena V.; Shevchenko, Olga S.; Semianiv, Ihor O.; Shevchenko, Rostyslav S.; Yeremenchuk, Inga V.; Shevchenko, Stanislav I.; Slyvka, Victor I.; Poteiko, Petro I.; Pidverbetskyi, Oleg Ya. (Balkan Medical Union, 2021)
Introduction. To date, there are virtually no data on pathomorphological changes in the mucous membrane of the small intestine in coinfection HIV/Mycobacterium tuberculosis (HIV/TB), which could be the basis for the development of malabsorption. The objective of the study was to investigate the pathomorphological characteristics of the small intestine mucosa in patients with coinfection HIV/TB. Materials and methods. The prospective pathomorphological study included 24 patients with HIV/TB coinfection (main group), and 20 patients without HIV infection, gastrointestinal pathology or morphological signs of TB (control group). Results. The thickness of the small intestine mucosa, the average height and width of villi were significantly lower in the HIV/TB group compared with the control group (p<0.05). The relative area of connective tissue in the small intestine mucosa was increased in the main group (p<0.05). The coefficient of variation of the optical density of nuclear chromatin in the main group noticeably exceeded the coefficient in the control group: 42.7±6.47% vs. 6.7±0.34% (p<0.05). The red/blue (R/B) ratio in the main group almost doubled that of the control group, while the quantitative index of the optical density of the specific colour for free amino groups was 1.7 times higher than in the control group (p<0.05). Conclusions. Coinfection HIV/TB is accompanied by the development of atrophic and sclerotic changes in the small intestine, a decrease in the functional activity of enterocytes and increased intensity of free radical processes.

Introduction. A ce moment, il n’y a pratiquement pas de données sur les modifications pathomorphologiques de la muqueuse de l’intestin grêle lors de la co-infection VIH/tuberculose, ce qui pourrait être à la base du développement d’une malabsorption. Le but de l’étude est d’étudier les caractéristiques de la structure morphologique de l’intestin grêle dans la tuberculose associée au VIH. Matériaux et méthodes. L’étude prospective pathomorphologique a inclus 24 patients avec co-infection VIH/Mycobacterium tuberculosis (groupe principal) et 20 personnes sans infection par le VIH, de pathologie gastro-intestinale ou de signes morphologiques de tuberculose (groupe témoin). Résultats. L’épaisseur de la petite muqueuse intestinale, la hauteur et la largeur moyennes des villosités étaient significativement plus petites dans le groupe VIH/tuberculose par rapport au groupe témoin (p<0,05). La surface relative du tissu conjonctif de la petite muqueuse intestinale était significativement plus élevée dans le groupe principal (p<0,05). Le coefficient de variation de la densité optique de la chromatine nucléaire dans le groupe co-infecté dépassait significativement celui du groupe témoin : 42,7±6,47% contre 6,7±0,34% (p<0,05). Le coefficient rouge/bleu (R/B) dans le groupe principal dépassait presque deux fois le même indicateur du groupe témoin, et l’indice quantitatif de la densité optique de la couleur spécifique pour les groupes amino libres était 1,7 fois plus élevé que dans le groupe témoin (p<0,05). Conclusions. La co-infection VIH/ tuberculose s’accompagne du développement de modifications atrophiques et sclérotiques de la paroi de l’intestin grêle, une diminution de l’activité fonctionnelle des entérocytes, signes d’une intensité accrue des processus des radicaux libres.
Les changements morphologiques de la membrane muqueuse de l’intestin grêle dans la co-infection VIH/Mycobacterium tuberculosis
Keywords: tuberculosis; HIV infection; small intestine; pathomorphology; la tuberculose; VIH infection; l’intestin grêle; la pathomorphologie